A boundary integral approach for plane analysis of electrically semi-permeable planar cracks in a piezoelectric solid - Ang, Whye Teong (2011)
A plane electro-elastostatic problem involving arbitrarily located planar stress free cracks which are electrically semi-permeable is considered. Through the use of the numerical Green's function for impermeable cracks, the problem is formulated in terms of boundary integral equations which are solved numerically by a boundary element procedure together with a predictor-corrector method. The crack tip stress and electric displacement intensity factors can be easily computed once the boundary integral equations are properly solved.